STUDENTS’ PERCEPTION TOWARDS TEACHER’S QUESTION IN CLASSROOM INTERACTION - Rizka Rahmadini Panggabean; Siti Aisah Ginting (Universitas Negeri Medan, 2022)
Teacher's question in the classroom activities are thought to help students learn more effectively. Successful learning in an English classroom should include knowledge of both the language and the material. In order for learning to be relevant and successful, questions in the English classroom should create opportunities for students to actively participate in the learning. Not only to promote classroom interaction, but also to encourage students to communicate in a real-life setting, to foster a closer relationship with the students, and to assist student with difficulty expressing themselves due to their limited vocabulary. The objective of this research were to (1) know about types of questions that frequently used by teacher in classroom interaction (2) identify students' perceptions of teacher while giving questions in English classes. The research was carried out from December 2021 to February 2022 on the teaching learning process in the XI RPL Class of SMKN 9 Medan. The data was gathered through an interview and questionnaire with 34 XI RPL 4 students, which is recorded and then transcribed. Students' perception data were analyzed by collecting data, reducing data, presenting data, and drawing conclusions. After that, the data was descriptively and qualitatively analyzed. The findings of this study were presented descriptively in order to fully reveal the students' perceptions. It was discovered that (1) when a teacher asks a question, students prefer referential questions over display questions. (2) the results of the questionnaire show that students had positive perception towards teacher's question in English classroom.